2015
DOI: 10.3329/bjid.v1i1.21473
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Sensitivity Pattern of Neisseria gonorrhoae Isolated from Women at a Tertiary Care Hospital in Dhaka City

Abstract: Background: Antibiotic sensitivity pattern of Neisseria gonorrhoae is changing frequently. Objective: The purpose of the present study was to see the antibiotic sensitivity pattern of Neisseria gonorrhoae isolated from women presented with cervicitis.Methodology: This cross sectional study.carried out in the Department  of Microbiology at Dhaka Medical College, Dhaka from July 2011 to December 2012 for a period of one and half year. All the women presented with or without the clinical features of  cervicitis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Again, most of the studies done in Bangladesh, concentrate on a single disease, pathogen, or specimen. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] But, a single organism can cause different types of infection, at different sites and can cause different diseases. For example, E. coli can cause gastroenteritis, sepsis, UTI, even meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…Again, most of the studies done in Bangladesh, concentrate on a single disease, pathogen, or specimen. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] But, a single organism can cause different types of infection, at different sites and can cause different diseases. For example, E. coli can cause gastroenteritis, sepsis, UTI, even meningitis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Various studies conducted in different parts of India reported high prevalence of gonorrhoea among HIV positive and 20–30 years of age group with male preponderance and risk factors such as low socio-economic status, unmarried, multiple sexual partners, living in urban area, profession involving long stay away from home, and past history of STI found to be associated with high prevalence of gonorrhoea. [ 5 , 6 ]…”
mentioning
confidence: 99%